2007
DOI: 10.1111/j.1365-2265.2007.02995.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of a protocol for reduced glucocorticoid replacement in transsphenoidal pituitary adenomectomy: prophylactic glucocorticoid replacement is seldom necessary

Abstract: Reduced glucocorticoid replacement in TSA is safe and reduces patient exposure to glucocorticoids and their potential adverse events. The occurrence of hypocortisolism in two low-risk subjects with serum cortisol > 250 nmol/l highlights the importance of daily clinical assessment when using this protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 15 publications
4
36
0
3
Order By: Relevance
“…In addition, we prospectively confirmed our previous results using POD1 cortisols in a retrospective cohort of 84 patients. Finally, these results corroborate and significantly extend the findings of Wentworth et al, in which the highest 8 am cortisol on the first, second, or third post-operative day determined the use of supplemental glucocorticoids; they found that all patients with a postoperative level C250 nmol/L (equivalent to 9.1 lg/dL) subsequently passed a 250 lg CST up to 24 months after surgery [29]. The protocol advocated by Wentworth requires a minimum stay until the morning of post-operative day 3 (a minimum of 72 h from the morning of surgery; the average length of stay in the study by Wentworth et al was 4.8 ± 0.3 nights), whereas common practice in our facility is for earlier discharge, with an average hospital stay, including surgery, of 47.1 ± 13.9 h and a median stay of 36 h in this cohort.…”
Section: Assessment Of Immediate Postoperative Cortisol Levelssupporting
confidence: 88%
“…In addition, we prospectively confirmed our previous results using POD1 cortisols in a retrospective cohort of 84 patients. Finally, these results corroborate and significantly extend the findings of Wentworth et al, in which the highest 8 am cortisol on the first, second, or third post-operative day determined the use of supplemental glucocorticoids; they found that all patients with a postoperative level C250 nmol/L (equivalent to 9.1 lg/dL) subsequently passed a 250 lg CST up to 24 months after surgery [29]. The protocol advocated by Wentworth requires a minimum stay until the morning of post-operative day 3 (a minimum of 72 h from the morning of surgery; the average length of stay in the study by Wentworth et al was 4.8 ± 0.3 nights), whereas common practice in our facility is for earlier discharge, with an average hospital stay, including surgery, of 47.1 ± 13.9 h and a median stay of 36 h in this cohort.…”
Section: Assessment Of Immediate Postoperative Cortisol Levelssupporting
confidence: 88%
“…In fact, although the patients suffered from general malaise and suffered anorexia, none were in danger of death from cardiovascular collapse. Based on this observation and supporting literature (Inder and Hunt, 2002; Wentworth et al, 2008) we have abandoned the routine use of peri-operative steroids for pituitary surgery for the last 10 years. The policy proved safe clinically, but we wanted to analyze these data to be sure that we were not being biased in our assessment.…”
Section: Introductionmentioning
confidence: 72%
“…variable según los estudios 5,[21][22][23][24][25][26][27] . Un meta-análisis concluyó que valores bajo 5 µg/dl y superiores a 13 µg/dl son altamente predictores de deficiencia e indemnidad del eje corticotrópico, respectivamente 15 , cifras inferiores a las propuestas en las guías clínicas 12 .…”
Section: Valor Predictivo De Eucortisolismo Del Cortisol Post-operatounclassified
“…Nuestro estudio concuerda con lo planteado por otros autores en el sentido de que valores sobre 15 µg/dl permiten predecir con alta seguridad la preservación del eje corticotropico post cirugía 5,12,21,28 . Si bien encontramos que pacientes con cortisol de 10 a 14,9 µg/dl también muestran preservación del eje, no es posible sacar conclusiones definitivas debido al número limitado de pacientes en este grupo (n = 5).…”
Section: Valor Predictivo De Eucortisolismo Del Cortisol Post-operatounclassified
See 1 more Smart Citation